Pengaruh Media Sosialisasi Pajak Berbasis Social Media Dan Subjective Norm Dalam Pemenuhan Kewajiban Perpajakan Dimoderasi Dengan Cost Compliance (Studi Pada Followers Akun Instagram @ditjenpajakRI) - Putri, Adinia Pitaloka; Pratiwi, Adhitya Putri; Septanta, Rananda (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This study aims to determine whether there is an influence of social media and subjective norms in fulfilling tax obligations. Then, to determine cost compliance of the moderating variables of each independent variable, namely social media-based social media and subjective norms. This type of research is quantitative research. The data used is primary data. The population in this study are followers of the Instagram account @ditjenpajakRI. The sample of this study amounted to 77 people and the sampling technique used snowball sampling. The data analysis model used in this research is multiple linear analysis and moderated regression analysis. Testing this research using IBM Statistics SPSS V.26. The results of this study indicate that social media-based social media and subjective norms have a significant effect on fulfilling tax obligations simultaneously or partially. The variable cost compliance is not able to moderate the relationship between social media in fulfilling tax obligations and cannot moderate the subjective norm in fulfilling tax obligations.ype your abstract here.